Analisis Rasio Keuangan Dalam Memprediksi Pertumbuhan Laba Pada PT. Garudafood Putra Putri Jaya, Tbk - Rosalina Tako; Agustinus Mantong; Helba Rundupadang (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to determine the effect of the current ratio (CR), debt to equity ratio (DER), net profit margin (NPM), and total asset turnover (TAT) on the profit growth of PT. Garudafood Putra Putri Jaya, Tbk period 2017-2022. This type of research is descriptive quantitative using secondary data. Data analysis was performed by multiple linear regression analysis using the t test, f test and determination test (R2). The results showed that the value of the current ratio (CR) did not affect profit growth, debt to equity ratio (DER) had an effect on profit growth, net profit margin (NPM) has an effect on growth and total asset turnover (TAT) has no effect on profit growth. While simultaneously CR, DER, NPM and TAT jointly affect old growth.